The rapid inhibition of B-cell activation markers by belimumab was associated with disease control in systemic lupus erythematosus patients - Wang, Jing; Ju, Bomiao; Zhu, Li; Li, Hanchao; Luo, Jing; Zhang, Jing; Hu, Nan; Mo, Lingfei; Wang, Yanhua; Pan, Ying; Huang, Jing; Lv, Xiaohong; et al. (Frontiers in Pharmacology, 2023)
To examine the kinetics of B cell subsets and activation markers in the early stage of belimumab treatment and their correction with treatment response, 27 systemic lupus erythematosus (SLE) patients were enrolled. Flow cytometry was used to test B cell subsets and activation markers (including CD40, CD80, CD95, CD21low, CD22, p-SYK and p-AKT). During belimumab treatment, SLEDAI-2K declined, the proportions of CD19+ B cells and naïve B cells decreased, whereas the switched memory B cells and non-switched B cells increased. The larger variations of the B cell subsets and the activation markers were in the first 1 month than the other later time frames. The ratio of p-SYK/p-AKT on non-switched B cell at 1 month was associated with the SLEDAI-2K decline rate in the 6 months of belimumab treatment. B cell hyperactivity was rapidly inhibited in the early stage of belimumab treatment, and the ratio of p-SYK/p-AKT may predict SLEDAI-2K decline.